2010
DOI: 10.1177/0040517510380777
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkle-resistant finishing of cotton fabric with BTCA - the effect of co-catalyst

Abstract: Fabrics treated with dimethyloldihydroxylethyleneurea (DMDHEU) are susceptible to formaldehyde release. High concentrations of formaldehyde have been reported to cause cancer in animal studies. Due to the toxicity of DMDHEU, the polycarboxylic acid class of non-formaldehyde crosslinking agents used for wrinkle-resistant treatment has been introduced. Among various researches, 1,2,3,4-butanetetracarboxylic acid (BTCA) is a desirable reactant when catalysed with sodium hypophosphite (SHP). The characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 13 publications
1
32
0
4
Order By: Relevance
“…The increase in curing time increased the crease recovery angle due to the formation of more esterification of cellulose and the Figure 5 shows its contribution is minimum when compared to silica nanoparticles and pH. improves the strength of the fabric 27 . Hence, the higher concentration of nano metal oxides results increases the strength of the cotton fabric and it is shown in Figure 7 The increase of curing time reduced the tensile strength of fabric due to more esterification (acid dehydration at high temperatures and high curing time) and cross linking, when it was treated with BTCA/SHP.…”
Section: Influence Of Process Parameters On Crease Recovery Anglementioning
confidence: 99%
See 1 more Smart Citation
“…The increase in curing time increased the crease recovery angle due to the formation of more esterification of cellulose and the Figure 5 shows its contribution is minimum when compared to silica nanoparticles and pH. improves the strength of the fabric 27 . Hence, the higher concentration of nano metal oxides results increases the strength of the cotton fabric and it is shown in Figure 7 The increase of curing time reduced the tensile strength of fabric due to more esterification (acid dehydration at high temperatures and high curing time) and cross linking, when it was treated with BTCA/SHP.…”
Section: Influence Of Process Parameters On Crease Recovery Anglementioning
confidence: 99%
“…Therefore, yellowing caused by citric acid and other hydroxyl multi functional carboxylic acids can probably be attributed to the formation of unsaturated polycarboxylic acids 26 . High acidity of chemicals is a source of causing fabric tendering and yellowing 27 , hence the pH increases the acidity level reduces and the whiteness of the fabric has been increased and it is shown in Figure 6. The increase in curing time and silica nanoparticles concentration gradually reduces the whiteness index of the fabric.…”
Section: Influence Of Process Parameters On Whiteness Indexmentioning
confidence: 99%
“…This is due to the fact that crosslinkers react with the hydroxyl groups in cellulose molecules with primary chemical bonds (Lam et al 2010;Trask-Morrell et al 1994;Sricharussin et al 2004;Dehadabi 2012;Peng 2012). Previous studies have shown that the crosslinking agents can interact with nanoparticles of titanium dioxide to improve the adhesion between cellulose molecules, but these carboxylic acids need to have at least two free carboxylic groups to be able to bind to both cotton and TiO 2 (Montazer et al 2012;Karimi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4-butanetetracarboxylic acid (BTCA), citric acid (CA), succinic acid (SUA), and malic acid (MLA) (Figure 1) are the most conventional polycarboxylic acid used as durable press finishing agents. Yellowing of fabric, deterioration of tensile strength, and also relative expensive cost of the reagents are the common drawbacks in finishing of cotton with polycarboxylic acids (Bhattacharyya, Doshi, & Sahasrabudhe, 2003;Chen, Yang, & Qiu, 2005;Lam, Kan, & Yuen, 2011;Martel, Morcellet, Ruffin, & Weltrowski, 2000;Martel, Weltrowski, Ruffin, & Morcellet, 2002;Sircharussin, Ryo-Aree, Intasen, & Poungraksakirt, 2004;Welch, 2001;Yang & Wang, 1996;Yang, Wang, & Kang, 1997). These disadvantages may be solved using polyamino carboxylic acids (PACAs).…”
Section: Introductionmentioning
confidence: 99%